2014
DOI: 10.5937/fmet1404329j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of spillover effect in system of active vibration control

Abstract: Experimental Investigation of Spillover Effect in System of Active Vibration Control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A feedback controller based on a reduced model can destabilize the residual modes. In function of sensor position the feedback can excite the un-modeled state of system (control spillover), and the sensor signals are contaminated by the residual modes (observation spillover) and degrade the active vibration system efficiency (Dong et al 2014;Jovanović et al 2014). Some methods for reduction of spillover effects are discussed by (Mei & Mace 2002;Kim & Inman 2001).…”
Section: Latin American Journal Of Solids and Structures 13 (2016) 26mentioning
confidence: 99%
“…A feedback controller based on a reduced model can destabilize the residual modes. In function of sensor position the feedback can excite the un-modeled state of system (control spillover), and the sensor signals are contaminated by the residual modes (observation spillover) and degrade the active vibration system efficiency (Dong et al 2014;Jovanović et al 2014). Some methods for reduction of spillover effects are discussed by (Mei & Mace 2002;Kim & Inman 2001).…”
Section: Latin American Journal Of Solids and Structures 13 (2016) 26mentioning
confidence: 99%
“…Flexible beam elements are distributed parameter systems with infinite Degrees of Freedom (DoF). The active vibration control generally requires a low-order mathematical model of the system containing a limited number of DoF [6]. In particular, care must be taken so that the control of low-frequency modes does not affect the stabilization of high-grade modes, since sensors and actuators have limited bandwidth [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is very important to specify the sensor and actuator position optimally to keep the control capability at maximum. Otherwise, control spillover and observation spillover may occur, and this will affect the efficiency of the control system [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found this method can achieve varying levels of success in the AVS applications ( Åström and Hägglund, 2004;Yatim and Darus, 2014). For example, Jovanović et al (2014) used the Z-N method to investigate the spillover effect of the AVS system on a composite beam and the vibration was reduced up to 94%.…”
Section: Introductionmentioning
confidence: 99%